Perceived organizational support in public and nonprofit organizations: Systematic review and directions for future research. (June 2023) - Prysmakova, Palina; Lallatin, Nicole
A qualitative meta-analysis of 57 studies (1987–2018) on perceived organizational support in public and nonprofit administrative contexts in various parts of the world revealed 70 related variables within 16 categories. While most reviewed studies sampled employees of the US, the UK, and Iran, in terms of geography, research on the perceived organizational support of public and nonprofit services has been constantly spreading and has been revealing similar findings across countries. While the article questions the generalizability of some findings due to the overreliance on small convenience samples from educational, health, and social work facilities, it supports the generalizability of many found associations even though they happen in various international, organizational, and institutional settings. In particular, in public-serving contexts, perceived organizational support exhibits stable and positive relationships with commitment, intent to stay, motivation, satisfaction derived from job and tasks, well-being, empowerment, reduced stress, work–family balance, and individual growth. Meanwhile, the positive perceptions of support link negatively to unionization and reveal no consistent patterns regarding demographics. The article invites scholars to explore public and nonprofit contexts further, and to test previously overlooked associations like those with leadership type, reward expectancy, public service motivation, and withdrawal activities. Points for practitioners: Perceived organizational support should be cultivated in public and nonprofit contexts, as it improves employees' commitment, motivation, satisfaction, and well-being, and reduces stress. Perceived organizational support might matter for retention more than the content of a job. Employees who feel supported demonstrate better work–family balance and positively perceive many aspects of their organizations. Promoting perceived organizational support helps when intensive workloads and high levels of stress are inadequately compensated. Perceived organizational support can mitigate employees' burnout caused by the emotional labor of service provision.